The Combined Poisson INMA(q) Models for Time Series of Counts - Kaizhi Yu; Hong Zou (Journal of Applied Mathematics)
A new stationary qth-order integer-valued moving average process with Poisson innovation is introduced based on decision random vector. Some statistical properties of the process are established. Estimators of the parameters of the process are obtained using the method of moments. Some numerical results of the estimators are presented to assess the performance of moment estimators.